Electromyographic activity assessment of individuals with and without temporomandibular disorder symptoms - Juliana de Paiva Tosato; Paulo Henrique Ferreira Caria (University of São Paulo, 2007)
INTRODUCTION: Temporomandibular disorders (TMD) present several signs and symptoms that hinder their correct diagnosis, which is imperative on the elaboration of a treatment plan. Over the past years, several studies have been conducted to characterize and classify TMD to better understand these disorders. Therefore, the purpose of this study was to assess the electromyographic behavior of the masseter and temporal muscles in individuals with and without myogenic, arthrogenic and mixed TMD. METHOD: Forty volunteers of both genders responded to the Research Diagnostic Criteria for Temporomandibular Disorders (RDC-TMD) Questionnaire, were submitted to clinical exam and underwent bilateral electromyographic exam of the masseter and temporal muscles. RESULTS: No statistically significant difference (p>0.05) was observed during the assessment of isotonic contraction. Regarding isometric contraction, pairing between the mixed TMD group and the asymptomatic subjects did not present significant difference (p>0.05). Comparison between the myogenic and arthrogenic TMD groups and the asymptomatic group showed statistically significant difference (p<0.05). The findings of the present study demonstrated alteration on the muscle contraction pattern of TMD individuals compared to that of asymptomatic patients.